Effects of joint screening for prostate, lung, colorectal, and ovarian cancer – results from a controlled trial - Fan, Zeyu; Zhang, Yu; Yao, Qiaoling; Liu, Xiaomin; Duan, Hongyuan; Liu, Ya; Sheng, Chao; Lyu, Zhangyan; Yang, Lei; Song, Fangfang; Huang, Yubei; Song, Fengju (Frontiers in Oncology, 2024)
Background: Although screening is widely used to reduce cancer burden, untargeted cancers are frequently missed after single cancer screening. Joint cancer screening is presumed as a more effective strategy to reduce overall cancer burden.Methods: Gender-specific screening effects on PLCO cancer incidence, PLCO cancer mortality, allneoplasms mortality and all-cause mortality were evaluated, and meta-analyses based on genderspecific screening effects were conducted to achieve the pooled effects. The cut-off value of timedependent receiver-operating-characteristic curve of 10-year combined PLCO cancer risk was used to reclassify participants into low-and high-risk subgroups. Further analyses were conducted to investigate screening effects stratified by risk groups and screening compliance.Results: After a median follow-up of 10.48 years for incidence and 16.85 years for mortality, a total of 5,506 PLCO cancer cases, 1,845 PLCO cancer deaths, 3,970 all-neoplasms deaths, and 14,221 allcause deaths were documented in the screening arm, while 6,261, 2,417, 5,091, and 18,516 outcomespecific events in the control arm. Joint cancer screening did not significantly reduce PLCO cancer incidence, but significantly reduced male-specific PLCO cancer mortality (hazard ratio and 95% confidence intervals [HR(95%CIs)]: 0.88(0.82, 0.95)) and pooled mortality [0.89(0.84, 0.95)]. More importantly, joint cancer screening significantly reduced both gender-specific all-neoplasm mortality [0.91(0.86, 0.96) for males, 0.91(0.85, 0.98) for females, and 0.91(0.87, 0.95) for meta-analyses] and all-cause mortality [0.90(0.88, 0.93) for male, 0.88(0.85, 0.92) for female, and 0.89(0.87, 0.91) for meta-analyses]. Further analyses showed decreased risks of all-neoplasm mortality was observed with good compliance [0.72(0.67, 0.77) for male and 0.72(0.65, 0.80) for female] and increased risks with poor compliance [1.61(1.40, 1.85) for male and 1.30(1.13, 1.40) for female].Joint cancer screening could be recommended as a potentially strategy to reduce the overall cancer burden. More compliance, more benefits. However, organizing a joint cancer screening not only requires more ingenious design, but also needs more attentions to the potential harms.